Effect of Sm on the cyclic stability of La–Y–Ni-based alloys and their comparison with RE–Mg–Ni-based hydrogen storage alloy. (8th February 2021) - Guo, Miao; Yuan, Huiping; Liu, Yuru; Jiang, Lijun
Abstract: The LaY2 Ni9.7 Mn0.5 Al0.3 and LaSm0.3 Y1.7 Ni9.7 Mn0.5 Al0.3 alloys have been synthesized to investigate the effect of Sm partial substitution for Y on the cyclic stability of A2 B7 -type La–Y–Ni-based alloys. Their cyclic properties were also compared with the A2 B7 -type (RE0.85 Mg0.15 )2 (NiAl)7 (RE = Rare Earth) alloys. The gas-solid and electrochemical cycle lives were tested. The structural stability, pulverization, and oxidation/corrosion performances were studied by X-ray diffraction (XRD), scanning electron microscopy (SEM), and electrochemical methods. The partial substitution of Sm for Y improves anti-corrosion and anti-pulverization performances, thereby increasing the cycle life of A2 B7 -type La–Y–Ni-based hydrogen storage alloys. The A2 B7 -type RE–Y–Ni-based alloys exhibit better crystal structure stability, but the gas-solid and electrochemical cyclic stability is worse than A2 B7 -type (RE0.85 Mg0.15 )2 (NiAl)7 alloys due to easier pulverization of particles and the oxidation of Y elements. Highlights: The degradation behaviors of RE–Y–Ni and RE–Mg–Ni alloys are first compared. HIA of RE–Mg–Ni alloys is more obvious than that of the RE–Y–Ni alloys. Corrosion and powdering resistance of RE–Y–Ni alloy are inferior to RE–Mg–Ni alloy. Sm element can enhance oxidation and pulverization resistance of RE–Y–Ni alloys. Partial substitution of Y by Sm reduces the structural stability in the early cycles.